2020
DOI: 10.1038/s41388-020-01431-8
|View full text |Cite
|
Sign up to set email alerts
|

HPV E2, E4, E5 drive alternative carcinogenic pathways in HPV positive cancers

Abstract: The dominant paradigm for HPV carcinogenesis includes integration into the host genome followed by expression of E6 and E7 (E6/E7). We explored an alternative carcinogenic pathway characterized by episomal E2, E4, and E5 (E2/E4/E5) expression. Half of HPV positive cervical and pharyngeal cancers comprised a subtype with increase in expression of E2/E4/E5, as well as association with lack of integration into the host genome. Models of the E2/E4/E5 carcinogenesis show p53 dependent enhanced proliferation in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 54 publications
0
64
0
1
Order By: Relevance
“…In HPV-associated HNSCC, Ren et al reported that different expression patterns of HPV genes are correlated with the integration status of the virus [ 95 ]. In 69 HPV-associated HNSCC cases in the TCGA dataset, those with HPV integration (+) disease showed a high expression of E6/E7 and low expression of E2/E4/E5, whereas those with HPV integration (−) disease showed a high expression of E2/E4/E5 and low expression of E6/E7.…”
Section: What Induces High Dna Methylation Subtypes?mentioning
confidence: 99%
“…In HPV-associated HNSCC, Ren et al reported that different expression patterns of HPV genes are correlated with the integration status of the virus [ 95 ]. In 69 HPV-associated HNSCC cases in the TCGA dataset, those with HPV integration (+) disease showed a high expression of E6/E7 and low expression of E2/E4/E5, whereas those with HPV integration (−) disease showed a high expression of E2/E4/E5 and low expression of E6/E7.…”
Section: What Induces High Dna Methylation Subtypes?mentioning
confidence: 99%
“…These observations imply that viral replication may involve DNA structure complexity that requires DNA repair to proceed. A plurality of HPV-associated cancers maintains episomal DNA copies of HPV genomes, which could be replication-competent [ 2 , 3 , 32 , 33 ], and E2, E4, and E5 can remain expressed in some HPV+ cancers [ 73 ]. How replication competence affects overall DSBR in HPV+ tumors is unclear, and a worthwhile comparison would be episomal only vs. integrated HPV+ cancers in terms of sensitivity to DNA damaging agents and DSBR pathway utilization.…”
Section: Proposed Mechanisms For Increased Radiosensitivity In Hpv+ Tumorsmentioning
confidence: 99%
“…In conclusion, the analysis of the effect of HPV infection on the epigenetic landscape of the host cell reveals an intricate network of interactions between viral and host proteins. Finally, while the viral oncoprotein E6 and E7 are the most extensively studied, a recent report from Ren et al investigated the oncogenic role of the episomal expression of the E2, E4 and E5 proteins [203]. Whole genomic expression analysis of pharyngeal and cervical cancers co-expressing E2, E4 and E5 showed a mechanism of carcinogenesis distinct from those found in tumors with HPV integration, and apparently characterized by fibroblast growth factor receptor (FGFR) pathway activation [203].…”
Section: Human Papillomavirus (Hpv)mentioning
confidence: 99%